FRI0082 Development of impairment, disability, radiological damage, comorbidity and mortality over 20 years in rheumatoid arthritis patients. (23rd January 2014) - Eberhardt, K.; Crnkic Kapetanovic, M.; Lindqvist, E.; Nilsson, J.-Å.; Saxne, T.; Pierre Geborek, P.G.
Abstract : Objectives: To study the development of impairment, disability, radiological damage, comorbidity and mortality over 20 years in a cohort followed prospectively from diagnosis. Methods: 183 RA patients diagnosed between 1985 and 1989 were prospectively monitored according to a standardised protocol over 20 years. Treatments followed clinical practice. There were 115 (63%) women, mean (SD) age was 51 (12) years and symptom duration before inclusion was 11 (7) months. Impairment was measured by signals of functional impairment (SOFI), a 3-parts performance based index measuring hand, arm and leg function, disability by health assessment questionnaire (HAQ), joint damage by Larsen score of radiographs of hands and feet, comorbidity by Charlson Comorbidity Index (17 diagnoses each weighted by mortality risk). Comorbidity was ascertained by scrutinizing medical records which are linked to national census registers to ascertain vital status. Due to mortality, both per protocol and last observation carried forward (LOCF) techniques were used. LOCF was used from baseline for comorbity, and from 10 years for the other variables. Data are given as means and 95% CI. Results: Impairment had a linear progression over the whole study period while disability progressed year 2-10 and then stabilised. Disease activity decreased year 1 and 2 and remained stable thereafter. Radiological damage progressed more rapidly year 1-5 and then gradually showed diminished progression rate. LOCF analyses did not change these analyses to any significant degree. Comorbidity increased the first 10 years but then stabilised in the per protocol analysis, but showed a steady increase over 20 years when using LOCF technique. Conclusions: Impairment measured by SOFI is much more progressive in RA over 20 years in this cohort diagnosed in the late 1980ies, compared to disability measured by HAQ where progression levelled off after 10 years. Radiographic damage increased most rapidly during the first 5 years. Disease activity was high in the beginning but stabilised after 2 years. Comorbidity measured by Charlson index showed a linear progression over time when using LOCF but not when using per protocol analyses. None of the other variables seemed sensitive to mortality as LOCF did not markedly change the results. Disclosure of Interest: None Declared